Effects of PAN‐based carbon fibers and its precursors on ethylenepropylenediene monomer insulations: Morphology and properties. Issue 9 (10th October 2017) - Zhang, Shuangkun; Zhang, Peng; Ali, Shafqat; Akram, Raheel; Wu, Dezhen; Wu, Zhanpeng
Abstract : The properties of ethylenepropylenediene monomer (EPDM) insulations are often inadequate for solid rocket motor (SRM) applications. These materials exhibit relatively high erosion rates during the operation of SRM unless they are reinforced with suitable fiber fillers. In this article, we report the findings of comprehensive mechanical and ablative studies of EPDM insulations blended with polyacrylonitrile (PAN) fiber, pre‐oxidized polyacrylonitrile fiber and carbon fiber using a two‐roll mill methodology. During the course of this investigation, PAN fiber‐filled EPDM insulations showed much superior mechanical and ablative properties than other fiber‐filled EPDM insulations. The microstructures of charred layers of these insulations after ablation were characterized by scanning electron microscopy. POLYM. COMPOS., 39:3336–3340, 2018. © 2017 Society of Plastics Engineers